IMPLEMENTASI KEBIJAKAN BANTUAN STIMULAN PERUMAHAN SWADAYA DI KABUPATEN MINAHASA SELATAN - REMBET, MEYER IMANUEL; LENGKONG, FLORENCE DAICY; LALOMA, ALDEN (Sam Ratulangi University, 2018)
This research aims to find out what caused the implementation of policies help self-help housing stimulantin South Minahasa Regency. This type of research is a qualitative descriptive study. Types of data used inthis research is the primary data and secondary data. The data collected by means of observation,interview and documentation. The analysis of the data used in this study, namely the reduction of data,data presentation, and conclusion. And from the research results show that implementation of the selfhelp housing assistance policy Stimulants in South Minahasa Regency: First, the size and purpose of thepolicy, that policy is very positive impact on the community. But there was a problem of society thatconsiders the system of recruitment of prospective recipients of this assistance are not completely wellunderway, the public assess the prospective recipient of the village is sometimes lost to people who have ahigh income is not that low so you can conclude that its application in the village are not right on target.Second, the policy resource can be judged from the issue of skill and the skill of employees here still needto be on the increase, particularly employees who have the engineering expertise of besic architects andcivil engineering or energy-experts in support the inaugural program help self-help housing stimulant.Third, the characteristics or properties of the agency/implementing agencies at the policy process canalready run by the Agency, Just an interesting question here is the program of assistance in disseminatingthe self-help housing is a stimulant in done by the technical team of the field can not walk properly,because only socializing through the village chief. Fourth, For communication between organizations,coordination with the authorities of the village should also be in more boost. The increase in the numberof recipients of assistance also needs to be carried out by the organisers. And fifth, the attitude of theexecutor, the executor is the attitude on the issue of discipline employees who are still very weak.Discipline in the meaning of discipline when it comes on time, break time and go home on time.Keywords: Implementation of Policy, Help of Stimulants, Self-help Housing